Zero Trust Architecture in Law Enforcement Mobile Governance: A Systematic Literature Review - Iwan Juniar Simanjutak; Dana Indra Sensuse (Jurnal Indonesia Sosial Sains, 2026)
The expansion of mobile government has changed the operational environment of law enforcement agencies. Officers increasingly access case records, location-based applications, biometric systems, cloud repositories, and digital evidence workflows through mobile and distributed endpoints. These conditions challenge perimeter-based security and raise questions about how Zero Trust Architecture can support secure, accountable, and rights-sensitive mobile governance. This study reviews recent literature to synthesize how Zero Trust Architecture can be positioned within law enforcement mobile governance. A systematic literature review was conducted using a PRISMA-based protocol. The search used Scopus as the primary database and applied English-language, open-access, article, and 2020–2026 filters. From 96 initial records, duplicate removal, title and abstract screening, and full-text eligibility assessment produced 40 included articles. The synthesis shows that the literature is dominated by Zero Trust Architecture migration, dynamic access control, authentication, Internet of Things, edge, and 6G security, while studies directly linking Zero Trust Architecture to police mobile governance remain scarce. Four cross-cutting themes were identified: continuous identity and device verification, context- and risk-aware policy enforcement, evidence and data governance, and organizational readiness. The article proposes a governance-oriented Zero Trust Architecture framework for law enforcement mobile systems that connects technical controls with legal accountability, auditability, and public trust. The review concludes that Zero Trust Architecture should be treated not only as a cybersecurity architecture but also as a policy instrument for strengthening secure mobile public service delivery.